EXPERIMENTAL EVALUATION OF BINARY CODES FOR CONSOLE DISPLAY. - Minor, Frank J.; Revesman, Stanley L. (Journal of Applied Psychology)
The article presents an evaluation of the operating coding performance of three binary code schemas to aid in the selection of a single code schema for a data processing system console display. The code schemas evaluated include Biquinary Code, Binary Coded Decimal and Combined Code. The efficiency of the programmer was measured in terms of the speed and accuracy of coding console address and character registers. The Binary Coded Decimal schema was found to be the most efficient in cost and electronic simplicity. It showed a significant time saving of 20-25% compared to the other 2 codes evaluated.